Molecular characterization of feline caliciviruses isolated from several adult cats with atypical infection showing severe flu-like symptoms on a remote island in Ehime, Japan - Nishisaka, Yuki; Fujii, Hikaru; Ono, Fumiko; Kadekaru, Sho; Kogiku, Hiroyuki; Une, Yumi; Takeguchi, Shione; Ohta, Naomi; Eto, Masumi; Takeuchi, Chiharu; Takeuchi, Seigou; Miki, Tetsuko; et al. (Virus research, 2025)
•Epidemic of atypical Feline calicivirus (FCV) in Aoshima Island, Japan.•Adult cats showed severe flu-like symptoms rarely accompanied by anemia and diarrhea.•Aoshima virulent strain likely mutated from typical FCV.•Aoshima virulent strain showed no serological cross-reactivity with an Osaka isolate.•Implications for FCV pathogenicity in cats. In November 2020, a volunteer group reported an outbreak of an infectious disease with a high fatality rate and flu-like symptoms among stray cats in Aoshima, a remote island in Ehime, Japan. Nine adult cats with severe symptoms were hospitalized. Feline calicivirus (FCV) was isolated from pharyngeal swabs of six hospitalized cats. An outbreak of virulent systemic FCV (VS-FCV) infection was initially suspected because of obvious flu-like symptoms in adult cats; however, no symptoms typically associated with VS-FCV, such as skin ulcers on the limbs, edema, or viremia, were observed. Notably, two of the hospitalized cats that showed severe disease had diarrhea and anemia, and died or had a prolonged illness. These cases reveal atypical symptoms of FCV infection that have not been previously reported. We further isolated typical strains from western Japan (Osaka, Kumamoto, and Ehime) and analyzed the viral genes along with virulent strains from Aoshima. Phylogenetic analysis showed that the Aoshima strain formed a new lineage distinct from known FCVs. The Aoshima strains isolated in the initial outbreak before December 5, 2020, and those isolated after the end of the outbreak, which are suspected pathogenic and typical non-pathogenic strains, respectively, were located in the same cluster and shown to be very similar in sequence. The virulent Aoshima strain, which causes atypical FCV infections in cats, may have been derived by acquiring several mutations from a typical strain that chronically infects cats on a remote island.